Analysis of financial time series - Tsay, Ruey S. (Wiley, 2005)
The tools provided in this text aid readers in developing a deeper understanding of financial markets through firsthand experience in working with financial data. This is an ideal textbook for MBA students as well as a reference for researchers and professionals in business and finance